2010
DOI: 10.1093/icb/icq062
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Phylogeny of Scleractinian Corals: A Review of Morphological and Molecular Data

Abstract: Scleractinian corals, which include the architects of coral reefs, are found throughout the world's oceans and have left a rich fossil record over their 240 million year history. Their classification has been marked by confusion but recently developed molecular and morphological tools are now leading to a better understanding of the evolutionary history of this important group. Although morphological characters have been the basis of traditional classification in the group, they are relatively few in number. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 47 publications
3
83
0
Order By: Relevance
“…Representative species of the two major clades of Scleractinia, Acropora yongei of the complex clade and Stylophora pistillata of the robust clade (19), were chosen for this study. We confirmed that coral VHA was expressed at the transcript level in A. yongei by RT-PCR of the VHA B subunit (VHA B ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Representative species of the two major clades of Scleractinia, Acropora yongei of the complex clade and Stylophora pistillata of the robust clade (19), were chosen for this study. We confirmed that coral VHA was expressed at the transcript level in A. yongei by RT-PCR of the VHA B subunit (VHA B ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as explicitly stated by the author, it had many points of uncertainty at subordinal and family levels. According to Budd et al (2010), this evolutionary scheme had even lower resolution among families and suborders than the classification of Wells (1956), and by that time cladistic analyses had yet to contribute significantly to our understanding of scleractinian evolution. Indeed, the use of morphological characters to establish phylogenetic relationships within coral families have proved challenging and, as a consequence, applied to only a small number of extant families-Fungiidae (Cairns 1984;Hoeksema 1989Hoeksema , 1991Hoeksema , 1993, Mussidae and Siderastreidae (Pandolfi 1992), Turbinoliidae (Cairns 1997), Faviidae (Johnson 1998), Acroporidae (Wallace 1999), Dendrophylliidae (Cairns 2001), Atlantic Faviidae and Mussidae (Budd and Smith 2005), and Pacific Faviidae (Huang et al 2009).…”
Section: Integrating Molecular and Morphological Evidencementioning
confidence: 99%
“…There was widespread acknowledgement that reclassification was necessary (Fukami 2008;Budd 2009;Budd et al 2010), but the convergence of most macromorphological characters conventionally used to define genera and families hindered revisionary work. Many molecular (Huang et al 2009(Huang et al , 2011Benzoni et al 2011;Arrigoni et al 2012;Schwartz et al 2012) and morphological (Budd and Smith 2005;Stolarski 2009, 2011) studies identified problematic taxa and highlighted phylogenetically informative charactersincluding molecular markers, macromorphology, micromorphology and microstructure-before the first taxonomic monograph was published.…”
Section: New Taxonomic Revisions Of Families and Generamentioning
confidence: 99%
“…In this study, we utilized immunohistochemistry to describe and compare the localization of three ion-transporting proteins that likely play a significant role in coral physiology: the Na ϩ /K ϩ -ATPase (NKA), the plasma membrane Ca 2ϩ -ATPase (PMCA), and putative bicarbonate transporters from the SLC4 family, in two distantly related species of branching scleractinian corals: Acropora yongei, from the complex clade, and Stylophora pistillata, from the robust clade (4). These two clades diverged ϳ250 -400 million years ago (Ma) (40,47) and are hypothesized to have independently evolved calcification (40).…”
mentioning
confidence: 99%